The Authority of Institutions to Prevent Corruption in Indonesia - Kasim, Ramdhan; Kadir, Yusrianto; Patawari,; Arif, Mohammad; Djanggih, Hardianto (International Journal of Psychosocial Rehabilitation, 2020)
The formation of the Corruption Eradication Commission (KPK) aims to facilitate and accelerate the eradication of corruption in Indonesia. Law No. 30 of 2002 concerning the Corruption Eradication Commission gives a very broad authority so that the KPK is called a "superbody" institution that has 5 tasks and 29 extraordinary powers. However, part of the authority is now limited, so it is feared that the role of the KPK in eradicating corruption in Indonesia will stagnate. After Law No. 30 of 2002 was revised into Law No. 19 of 2019 concerning the Corruption Eradication Commission, the Corruption Eradication Commission became a state institution in the executive power cluster that is independent and free from the influence of any power, and the Corruption Eradication Commission (KPK) employee is a state civil apparatus (ASN) as referred to in the legislation concerning the state civil apparatus. Before the revision, the KPK was independent, and the KPK employees were recruited independently and became permanent KPK employees. After the revision, the KPK can stop the investigation and prosecution of corruption cases, and the KPK no longer has the authority to appoint and dismiss investigators as investigators at the KPK. All KPK activities are supervised by the Supervisory Board so that the wiretapping is carried out after obtaining written permission from the Supervisory Board.